Contribution of shorter-term radiative forcings of aerosols and ozone to global warming in the last two decades - Qing-Bin Lu (AIP Advances)
This paper reports observations of regional and global upper stratosphere temperature (UST) and surface temperature, as well as various climate drivers, including greenhouse gases (GHGs), ozone, aerosols, solar variability, snow cover extent, and sea ice extent (SIE). We strikingly found warming trends of 0.77(±0.57) and 0.69(±0.22) K/decade in UST at altitudes of 35–40 km in the Arctic and Antarctic, respectively, and no significant trends over non-polar regions since 2002. These UST trends provide fingerprints of decreasing and no significant trends in total GHG effect in polar and non-polar regions, respectively. Correspondingly, we made the first observation of surface cooling trends in both the Antarctic since 2005 and the Arctic since 2016 once the SIE started to recover. However, surface warming remains at mid-latitudes, which caused the recent rise in global mean surface temperature (GMST). These temperature changing patterns are consistent with the characteristics of the cosmic-ray-driven electron reaction (CRE) mechanism of halogen-containing GHGs (halo-GHGs) with larger destruction rates at higher latitudes. Moreover, the no-parameter physics model of warming caused by halo-GHGs closely reproduces the observed GMSTs from 2000 to 2024, including the pause in warming during 2000–2012 and the significant warming by 0.2–0.3 °C during 2013–2023, of which 0.27 °C was calculated to arise from the net radiative forcing of aerosols and ozone due to improved air quality. The results also show that the physics model captures 76% of the variance in the observed GMSTs, exhibiting a warming peak in October 2023 and predicting a gradual GMST reversal thereafter.